Characterization of Corrosion Behavior of TA2 Titanium Alloy Welded Joints in Seawater Environment - Zhang, Dalei; Liu, Yingshuang; Liu, Ran; Guan, Xiaorui; Xing, Shaohua; Dou, Xiaohui; He, Zonghao; Zhang, Xinwei (Frontiers in Chemistry, 2022)
Titanium alloy has been widely used in Marine pipeline system because of its excellent corrosion resistance. However, there are differences in microstructure and electrochemical properties because of the heterogeneous structure of the welded joint, the corrosion behavior is often different. In this paper, the corrosion behavior of TA2 titanium alloy welded joint in seawater at different temperatures was studied by traditional macro electrochemical test analysis combined with microelectrode array test and surface morphology analysis. Conventional macroscopic electrochemical analysis results show that the corrosion resistance of heat-affected zone is always the best, followed by the base metal and the weld. And the higher the temperature, the easier the formation of passivation film. The results of microelectrode array test show that the heat-affected zone is always the cathode region of the whole welded joint, and part of the cathode near the base metal region has the largest current density, which acts as the main cathode to slow down corrosion. At slightly higher temperatures, the polarity deflection will occur in the base metal zone and weld zone due to the different formation speeds of passivation film in early corrosion stage. With the prolongation of corrosion time, the base metal eventually becomes the cathode zone and the weld zone eventually becomes the anode zone.